(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2025)
Background: Tumor-infiltrating mast cells have been reported to play functional roles in the tumor microenvironment. However, controversial evidence exists regarding their impact on different cancers. The present study aimed to determine tumor-infiltrating Mast Cell Density (MCD) in gastric adenocarcinoma and its relationship with clinicopathological parameters. Materials and methods: Fifty cases of gastric adenocarcinoma were included in this study from the Department of Surgery of Chittagong Medical College Hospital from September 2020 to June 2022. Gastrectomy specimens were sectioned and stained with routine Hematoxylin and Eosin stain. Toluidine blue stain was used to calculate MCD. Results: The mean age of the patients was 56.9±9.6 years (Range: 30-75), 56% were male, and the mean MCD was 7.13±2.85. Mean MCD was similar in patients aged <60 years and 60 years (p=0.186) and in male and female patients (p=0.654). MCD was statistically significantly increased in poorly differentiated tumors (11.25±1.24) than in moderately differentiated (6.11±1.24) and well differentiated (3.85±1.18) adenocarcinoma. Increasing MCD was observed with the higher tumor stages (4.93±1.48, 7.17±3.02, and 7.54±2.80 in tumors with pT1, pT2, and pT3 stage, respectively, without any statistical significance (p=0.175). Conclusion: The study suggests that mast cells play a role in the tumor development and progression in gastric adenocarcinoma. Understanding the role of mast cells in this context can help develop targeted therapies and improve patient outcomes. JCMCTA 2025 ; 36 (1) : 82-87